Laryngeal Carcinoma Characteristics Associated with Positive Margins and Endoscopic Understaging - Nia Labaš; Andro Košec; Mirta Peček; Tomislav Gregurić; Siniša Stevanović (Diagnostics)
Background/Objectives: The study aims to analyse the factors associated with positive margins and endoscopic understaging in laryngeal carcinoma. It also aims to assess the diagnostic accuracy of Narrow Band Imaging (NBI) in comparison to White Light Endoscopy (WLE) and other diagnostic methods. Methods: In this retrospective comparative cohort analysis, 206 patients who underwent endoscopic laser surgery for T1 and T2a glottic squamous cell carcinoma between 1 January 2016 and 30 April 2023 were included. The data were collected from endoscopy, CT, histopathology, and NBI images. Statistical analysis was performed and associations between variables were analysed using binary logistic regression and receiver operating characteristic analysis. Results: The types of cordectomy performed included type III (51 patients), type IV (40 patients), and type VI (23 patients). Positive margins were found in 14.01% of patients, with significant correlations observed between positive margins and bilateral laryngeal carcinoma, right-sided laryngeal carcinoma, higher clinical and histopathologic T categories, and higher NBI grade. Endoscopic understaging versus histopathologic T category correlated with various factors, including cordectomy type, tumour size, and clinical T category. The NBI findings correlated with positive margins but did not correlate with endoscopic understaging. Conclusions: The study highlights several clinical and pathological factors associated with positive margins and endoscopic understaging in laryngeal carcinoma. NBI demonstrated high diagnostic accuracy, correlating with histopathological results and serving as an independent predictive factor for positive margins. Recognizing these factors is crucial for improving preoperative assessments, refining treatment strategies, and enhancing patient care.